Novel proton MR spectroscopy findings in adenylosuccinate lyase deficiency. Issue 4 (10th October 2012) - Zulfiqar, Maria; Lin, Doris D.M.; Van der Graaf, Marinette; Barker, Peter B.; Fahrner, Jill A.; Marie, Sandrine; Morava, Eva; De Boer, Lonneke; Willemsen, Michel A.A.P.; Vining, Eileen; Horská, Alena; Engelke, Udo; et al.
Abstract Adenylosuccinate lyase (ADSL) deficiency is a rare inborn error of metabolism resulting in accumulation of metabolites including succinylaminoimidazole carboxamide riboside (SAICAr) and succinyladenosine (S‐Ado) in the brain and other tissues. Patients with ADSL have progressive psychomotor retardation, neonatal seizures, global developmental delay, hypotonia, and autistic features, although variable clinical manifestations may make the initial diagnosis challenging. Two cases of the severe form of the disease are reported here: an 18‐month‐old boy with global developmental delay, intractable neonatal seizures, progressive cerebral atrophy, and marked hypomyelination, and a 3‐month‐old girl presenting with microcephaly, neonatal seizures, and marked psychomotor retardation. In both patients in vivo proton magnetic resonance spectroscopy (MRS) showed the presence of S‐Ado signal at 8.3 ppm, consistent with a prior report. Interestingly, SAICAr signal was also detectable at 7.5 ppm in affected white matter, which has not been reported in vivo before. A novel splice‐site mutation, c.IVS12 + 1/G > C, in the ADSL gene was identified in the second patient. Our findings confirm the utility of in vivo proton MRS in suggesting a specific diagnosis of ADSL deficiency, and also demonstrate an additional in vivo resonance (7.5 ppm) of SAICAr in the cases of severe disease. J. Magn. Reson. Imaging 2013;37:974–980. © 2012 Wiley Periodicals, Inc.